Berberine influences multiple diseases by modifying gut microbiota - Yang, Fujie; Gao, Rongmao; Luo, Xiaoxiu; Liu, Rongan; Xiong, Daqian (Frontiers in Nutrition, 2023)
Berberine (BBR) is an isoquinoline alkaloid that is widely distributed in the plant kingdom and is commonly found in Coptis chinensis Franch.It has low bioavailability, but it can interact with gut microbiota and affect a variety of diseases. The effects of BBR in diabetes, hyperlipidemia, atherosclerosis, liver diseases, intestinal diseases, mental disorders, autoimmune diseases, and other diseases are all thought to be related to gut microbiota. This review systematically and comprehensively summarize these interactions and their effects, and describes the changes of gut microbiota after the intervention of different doses of berberine and its potential clinical consequences, in order to provide a basis for the rational application of BBR in the future clinical treatment.